MANTRA MASYARAKAT BANTEN (Kajian Etnografi di Kabupaten Tangerang) (POETIKA, 2022)
The purpose of this research is to describe the mantra of Tangerang Regency of Banten. The  method used in this study, the author uses qualitative approach with ethnography method. ethnography method is one of qualitative research strategy in which researcher investigates a cultural group in the natural environment for the main data collection in long period of time. The data in this research are in the forms of community mantra of Tangerang Regency which are taken from 29 resource persons who are the residents in Tangerang Regency spreaded in 29 Districts. To analyze the data, the authors used domein analysis, taxonomic analysis, and component analysis. From the research result the researcher obtained data in the form of seven mantra classifications, they are (1) Mantra ajian, (2) asihan, (3) jampe, (4) jangjawokan, (5) rajah, (6) pellet/pekasih, and (7) singular. The elemental structure builds rhymes, dictions, images, and majas. The use and function of mantra is to repellent the reinforcement, subjugate the heart of a person and also the education system in the daily life of the people in Tangerang Regency of Banten.